Dinamika Resiliensi pada Co-Founder Startup Generasi Milenial - Eva Rahman (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
Abstract. The formation of startup in Indonesia that sharply increase, have inspires milenial to do the same. But in its formation, there are various failures that must be faced. Startup co-founder who has multiple roles in the company, requires good resilience ability to faces problems. This study aims to determine the resilience dynamics of the millennials generation startup co-founder when facing the challenges in forming their startup. The qualitative-phenomenological approach was carried out through semi-structured in-depth interviews and observations, on 4 participants who were selected by purposive sampling, with the criteria (1) being a co-founder of startup that has been established for at least 2 years, (2) when being a co-founder they were still as a college student, (3) millennials generation (born at 1980-2000). The data validity technique was carried out by method triangulation, time triangulation, and member checking. Data analysis was carried out using Interpretative Phenomenological Analysis. The results show that there are three phases of the millennials startup co-founder resilience dynamics, (1) the initial phase, in the form of self-actualization motivation and the trend of establishing startup; (2) the stress phase, in the form of co-founder task stressors, academic, social, and expectations; (3) the adaptation & awakening phase, in the form of coping mechanisms and support systems. The results of the study can be used as a reference for millennials startup co-founders to build resilience. Further studies by increasing the number of participants, and using more reliable theory, are highly recommended to increase the validity of the findings.